2010
DOI: 10.4269/ajtmh.2010.09-0724
|View full text |Cite
|
Sign up to set email alerts
|

Can Daytime Use of Bed Nets Not Treated with Insecticide Reduce the Risk of Dengue Hemorrhagic Fever Among Children in Vietnam?

Abstract: The purpose of this study was to investigate the prevalence of bed net use and elucidate the effect of daytime bed net use on preventing dengue hemorrhagic fever (DHF) among children in Vietnam. We conducted a population-based cross-sectional survey and a matched case–control study in Khanh Hoa Province where not only some pre-schoolchildren but also some school children, who take a nap during lunch break prior to returning to school, used bed nets during the day. Among 36,901 children 2–10 years of age, most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
2
5
0
3
Order By: Relevance
“…Consistent with other studies, we observed a significant association of both DENV seroprevalence and seroconversion with use of some personal mosquito control measures [11,5960]. In our evaluation of the effect of personal mosquito control measures on the risk of dengue infection, bed nets appeared to be associated with a lower likelihood of infection than the use of mosquito coils or insecticide sprays, which is consistent with findings reported by others [61]. This pattern might reflect the overall inefficiency of some of these devices (e.g., mosquito coils or sprays) to reduce vector populations, or using them at inappropriate times (i.e., at night rather than in the daylight hours when Ae .…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies, we observed a significant association of both DENV seroprevalence and seroconversion with use of some personal mosquito control measures [11,5960]. In our evaluation of the effect of personal mosquito control measures on the risk of dengue infection, bed nets appeared to be associated with a lower likelihood of infection than the use of mosquito coils or insecticide sprays, which is consistent with findings reported by others [61]. This pattern might reflect the overall inefficiency of some of these devices (e.g., mosquito coils or sprays) to reduce vector populations, or using them at inappropriate times (i.e., at night rather than in the daylight hours when Ae .…”
Section: Discussionsupporting
confidence: 92%
“…aegypti that come into contact with them, as shown in trials in Haiti [ 60 ]. However, the protective role of bed nets against DENV infections has been debated in the literature, as other studies have failed to find an association between mosquito bed net use and DENV infections [ 61 , 62 ], presumably because Ae . aegypti feeds during the day (morning and afternoon) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti that come into contact with them, as shown in trials in Haiti [58]. Other studies have failed to find an association between mosquito net use and DENV infections [59,60], presumably because Ae. aegypti feeds during the day (morning and afternoon) [61].…”
Section: Discussionmentioning
confidence: 99%